STATUS KLINIS DAN DETEKSI LipL32 SAPI SEROPOSITIF LEPTOSPIROSIS DI KABUPATEN KULON PROGO - Guntari Titik Mulyani; Wayan Tunas Artama; Estu Widodo (Jurnal Sain Veteriner, 2021)
Leptospirosis is a zoonotic disease caused by Leptospira interrogans. Animals can act as carriers, spread leptospires in urine, and be a source of infection for other animals and humans. In leptospirosis cows can cause abortion, early birth, infertility, decreased milk production and death. The aims of this study was to determine the clinical status and detect the presence of leptospires with Polymerase Chain Reaction (PCR) from urine cows that are expressed as leptospirosis seropositive. A total of 12 cattle seropositive leptospirosis with Microscopic Agglutination Test (MAT) were carried out clinical examinations covering general conditions, pulsus examination, breathing and temperature and organ systems. The urine is collected aseptically, then DNA isolation is carried out using a kit from Genoid. Detection of leptospires in the urine is carried out by detecting the presence of the primary lipoprotein LipL32 making up the Leptospira membrane. The primer was designed with a 21-base forward forward: 5'-TGG ATC TGA TCA ACT ATT ACG-3 ‘containing 38.1% GC with Tm 57.2oC. 22 bases reverse reverse obtained: 5 '-CAC TTC ACC TGG TTT GTA GGT-3' containing GC 45.5% with Tm 62.1oC. Amplification was carried out as many as 40 cycles and continued with electrophoresis to determine the band formed at a wavelength of 506 bp. The results showed that all cows that were positive for leptospirosis with MAT were in a clinically healthy condition. In electrophoresis there are 7 out of 12 positive samples found in the urine leptospira indicated by the formation of a band at 506 bp. From the results of this study it can be concluded that leptospirosis-positive cows do not always show clinical symptoms, but have the potential to excrete leptospires along with urine, so they can act as a source of transmission of leptospirosis to humans, other animals, and the environment.